Incidence and Presentation of Molar Pregnancy at Bahawal Victoria Hospital, Bahawalpur - NOREEN AKMAL, NAILA IHSAN, TASNEEM AKHTAR, ASLAM MEHMOOD MALIK (Journal of Fatima Jinnah Medical University, 2018)
Background: Molar pregnancy is the most common form of gestational trophoblastic neoplasia. Incidence of molar pregnancy varies globally and appears to be higher in south east Asia. The objective of this study was to find out the incidence and presentation of molar pregnancy at Bahawal Victoria Hospital Bahawalpur. Patients and Methods: A 6 year retrospective, descriptive study conducted at Gynae Unit-II of Bahawal Victoria Hospital, Bahawalpur, from 1st January 2007 to 31st December 2012. Diagnosis of molar pregnancy was made on the basis of history, physical examination and investigations. The incidence and mode of clinical presentation was noted. Results: A total of 102 cases of molar pregnancies were reported and the incidence of molar pregnancy was 4.17 / 1000 live births during the study period. The mean age of the patients was 31.1 years. 44 (43.1%) patients were either Para 0 or Para 1 while 34 (33.3%) were Para 4 or above. Majority of the patients, 75 (73.5%) were diagnosed during the first trimester. All the patients reported amenorrhea while abnormal vaginal bleeding (92.1%) and uterus size enlargement of more than 4 weeks (81.3%) were the commonest clinical presentations. Conclusion: The incidence of molar pregnancy is 4.17 / 1000 live birts in the study population. Most common mode of presentation is abnormal vaginal bleeding and uterine enlargement.